A Technology Overview and Future Scope of Bio-Mems in Tropical Disease Detection: Review - Katta, Miranji; R, Sandanalakshmi (International Journal of Engineering and Technology, 2018)
From past few years, there is a revolutionary progress in biomedical sensing applications as a result of incredible growth in technological advancements. The biomedical sensors play a key role in the global market and it is estimated to reach 15.01 Billion US$ by 2022. As a worldwide research focus, there is especially a strong interest in the use of micro and Nanosystems in health monitoring. Most of the researchers applying innovative techniques to noninvasive patient monitoring and diagnostics developed with micro and nanofabricated technologies like MEMS/NEMS. Which provides more compact, inexpensive, accurate, and reliable detection tools to identify more life-threatening diseases in early times. This review paper will focus on various tropical disease detection methods and scope of the BioMEMS towards the detection of more prevalent tropical diseases.
Keywords: MEMS; biosensors; actuators; tropical diseases; noninvasive; chemical sensing; microfluidics; biotechnology.